2011
DOI: 10.1164/rccm.201006-0980oc
|View full text |Cite
|
Sign up to set email alerts
|

A3 Receptors Are Overexpressed in Pleura from Patients with Mesothelioma and Reduce Cell Growth via Akt/Nuclear Factor-κB Pathway

Abstract: These new findings suggest that A₃AR could represent a pharmacological target to prevent tumor development after asbestos exposure and to treat full-blown MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 46 publications
0
58
0
Order By: Relevance
“…Inhibition of Akt is triggered by A 3 AR for the reduction of LPS-mediated hypoxiainducible-factor 1a (HIF-1a) accumulation in murine astrocytes . Downregulation of the PI3K/Akt-NF-kB signaling pathway has also been observed in the inhibitory effect of IB-MECA in adjuvantinduced arthritis and in mesothelioma Madi et al, 2007;Varani et al, 2011a). Recently, it was reported that A 3 AR suppresses angiogenesis by inhibiting PI3K/Akt/mammalian target of rapamycin signaling in endothelial cells (Kim et al, 2013).…”
Section: Intracellular Pathways Regulated By the Amentioning
confidence: 96%
See 1 more Smart Citation
“…Inhibition of Akt is triggered by A 3 AR for the reduction of LPS-mediated hypoxiainducible-factor 1a (HIF-1a) accumulation in murine astrocytes . Downregulation of the PI3K/Akt-NF-kB signaling pathway has also been observed in the inhibitory effect of IB-MECA in adjuvantinduced arthritis and in mesothelioma Madi et al, 2007;Varani et al, 2011a). Recently, it was reported that A 3 AR suppresses angiogenesis by inhibiting PI3K/Akt/mammalian target of rapamycin signaling in endothelial cells (Kim et al, 2013).…”
Section: Intracellular Pathways Regulated By the Amentioning
confidence: 96%
“…Finally, very high A 3 AR protein expression was observed in a variety of cancer cell lines (Gessi et al, , 2007Merighi et al, 2001Merighi et al, , 2009Suh et al, 2001;Morello et al, 2009;Jajoo et al, 2009;Cohen et al, 2011;Hofer et al, 2011;Varani et al, 2011aVarani et al, , 2013Kanno et al, 2012;Nogi et al, 2012;Kamiya et al, 2012;Otsuki et al, 2012;Vincenzi et al, 2012;Nagaya et al, 2013;Sakowicz-Burkiewicz et al, 2013;Madi et al, 2013) and in cancer tissues (Gessi et al, 2004a;Madi et al, 2004;Bar-Yehuda et al, 2008;Varani et al, 2011a), thus suggesting a role for this subtype as a tumoral marker.…”
Section: Distribution Of the A 3 Adenosine Receptormentioning
confidence: 99%
“…Capadenoson (15) (Ohaion et al, 2009;Varani et al, 2010Varani et al, , 2011. The physiology of A 3 signaling is especially complex because of major differences between rodent and primate species in receptor function and tissue distribution.…”
Section: Synthetic Adenosine Receptor Agonistsmentioning
confidence: 99%
“…Finally, adenosine is also active on tumor cells (7). However, it is not yet clear whether administration of P1 agonists or antagonists will be beneficial or detrimental, due to the different P1 subtypes expressed and the different dosedependent effects on proliferation, VEGF release, and apoptosis; current evidence suggests that targeting A3 receptors might be a promising anticancer strategy (63).…”
Section: Purinergic Signaling and Cancer Therapymentioning
confidence: 99%